IDEALS OF A CREATIVE PERSON (In the Example of the Novels of Isajon Sultan and Paulo Coelho) (American Journal of Business Management, Economics and Banking, 2023)
This article analyzes the ideals of a creative person. The views of the author are studied on the example of the works of I. Sultan and P. Coelho. Analytical opinions are also presented regarding the opinions of these writers about creativity.